Comparative Study of Tafsir Marah Labid and Al-Azhar in Interpreting Mutasyabihat Verses Regarding Lafazh Istiwa - Fiddarain, Zaduna; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
Scholars divide the verses of the Qur'an into two categories: muhkam and mutasyâbihat. One of the most hotly discussed topics is how to interpret the verses in mutasyâbihat that deal with Allah's characteristics. As such, we talk about mutasyabihat verses concerning the qualities of Allah, but we limit our discussion to the lafazh istiwa in this instance. We shall talk about the Nusantara mufassirs' comparative interpretations of the verses about the characteristics of Allah SWT regarding the lafazh Istiwa found in Marah Labid, and in Syaikh Nawawi al-Jawi's interpretation of Al-Azhar.